Enhancing the quality of life: Prosthetic rehabilitation of nasal defect - Natarajan Kalavathy; Janakirama Reddy Sridevi; Sunitha Roy; Neeladri Verma; Sonali Chhabria (Wolters Kluwer Medknow Publications, 2014)
Face is an important part of one's personality and body image. Facial disfigurement can have extremely negative psychological impact on any individual, which may include feeling of being ugly, deformed, disfigured, and complete loss of self-confidence. A facial prosthesis is fabricated to restore any such anatomical compromise, which can be congenital, due to trauma or oral/facial malignancies. Patients who need such prosthesis usually present a wide array of rehabilitation challenges mainly associated with restoring normal appearance. The following case report illustrates the prosthetic rehabilitation of a 9-year-old boy who was diagnosed with basal cell carcinoma of the nose and underwent partial rhinectomy. Surgical reconstruction was also done for the same, which was unsuccessful due to failure of graft. This led to loss of right lateral ala of the nose and depression of the upper half of the bridge of the nose. This case was then prosthetically managed with a spectacle retained nasal prosthesis made up of acrylic.